Climatic records and linkage along an altitudinal gradient in the southern slope of Nepal Himalaya (Journal of Nepal Geological Society, 2017)
To validate the climatic linkages under different topographic conditions, observational climate data at four automated weather stations (AWS) in different elevations, ranging from 130 m asl. to 5050 m asl., on the southern slope of the Nepal Himalayas was examined. the variation of means and distribution of daily, 5-days, 10-days, and monthly average/sum of temperature/ precipitation between the stations in the different elevation was observed. Despite these differences, the temperatures records are consistent in different altitudes, and highly correlated to each other while the precipitation data shows comparatively weaker correlation. The slopes (0.79-1.18) with (R2 >0.64) in the regression models for high Mountain to high Himalaya except in November and 0.56-1.14 (R2 >0.50) for mid-hill and high Mountain except January, December, June indicate the similar rate of fluctuation of temperature between the stations in the respective region. These strong linkages and the similar range of fluctuation of temperature in the different elevation indicate the possibilities of their use of lower elevation temperature data to represent the higher elevation sites for paleoclimatic calibration. However, the associations of precipitation between the stations at the different elevation are not as strong as the temperature due to heterogeneous topographical features and steep altitudinal contrast.